Franz Kafka's A Country Doctor & other fantastic films [1987-2007] - Yamamura, Koji ([s.l.] : Kimstim, 2010)
Kafuka Inaka Isha = Franz Kafke Ein Landarzt = [A country doctor (21 min. ; 2007) ## A child's metaphysics = Kodomo no keijijogaku (5 min. ; 2007) ## The old crocodile = [Toshi wo totta wani] (13 min. ; 2005)## Pieces = Omake (2 min. ; 2003) ## Mt. Head = Atama yama (10 min. ; 2002)## Your choice! = Docchi ni suru? (10 min. ; 1999) ## Bavel's Book = [Bavel no hon] (5 min ; 1996) ## Kids castle (5 min. ; 1995) ## Kipling Jr. (15 min. ; 1995) ## Karo to puyobuputo = [Karo & piyoubupt series] (3 episodes, 4 min. each ; 1993) ## Enkinhou no hako : hakase no sagashimono = Perspektivenbox : the researcher's search (4 min. ; 1989) ## Suisei = [Aquatic] (5 min. ; 1987) ## Hyakka zukan = Japanese-English pictionary (4 min. ; 1989)
In Japanese or English with English subtitles.
film
Keywords: Yamamura, Koji